Advances in User Modeling UMAP 2011 Workshops, Girona, Spain, July 11-15, 2011, Revised Selected Papers - Ardissono, Liliana; Kuflik, Tsvi.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2012)
This book constitutes selected papers from the lectures given at the workshops held in conjunction with the User Modeling, Adaptation and Personalization Conference, UMAP 2011, Girona, Spain, in July 2011. The 40 papers presented were carefully reviewed and selected for inclusion in this book. For each workshop there is an overview paper summarizing the workshop themes, the accepted contributions and the future research trends. In addition the volume presents a selection of the best poster papers of UMAP 2011. The workshops included are: AST, adaptive support for team collaboration; AUM, augmenting user models with real worlds experiences to enhance personalization and adaptation; DEMRA, decision making and recommendation acceptance issues in recommender systems; PALE, personalization approaches in learning environments; SASWeb, semantic adaptive social web; TRUM, trust, reputation and user modeling; UMADR, user modeling and adaptation for daily routines: providing assistance to people with special and specific needs; UMMS, user models for motivational systems: the affective and the rational routes to persuasion.
Keywords: Computer science; Artificial intelligence; Computer simulation; Social sciences -- Data processing; Computer Science; User Interfaces and Human Computer Interaction; Artificial Intelligence (incl. Robotics).; Information Systems Applications (incl. Internet).; Simulation and Modeling; Computers and Society; Computer Appl. in Social and Behavioral Sciences